Konsistensi Perubahan Bunyi Morfem Dalam Bahasa Jawa - Wijayanti, Kenfitria Diah; Rahadini, Astiana Ajeng; Veronika, Prima (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to describe the forms and background of morpheme sound changes in Javanese. This research is a descriptive qualitative study. The data in this article consists of lexicons or vocabulary found in everyday Javanese speech. The data source for this study comes from the Javanese community in Surakarta. The subject selection technique was purposive sampling. Data collection was conducted using listening and note-taking techniques. Data validity was tested using theoretical triangulation and source triangulation. Meanwhile, the data analysis technique used was the Spradley model. The Spradley model consists of four stages: domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. Based on the data analysis, the following conclusions can be drawn. There are six forms of morpheme sound changes in Javanese, driven by the demands of (1) krama; (2) guru lagu; (3) guru wilangan; (4) literer; (5) jenis seks; (6) informalization of variety.